Other Americans : the art of Latin America in the US imaginary - Bush, Matthew, 1976- (Pittsburgh, Pa. : University of Pittsburgh Press, 2022)
"Grounded in perspectives of affect theory, Other Americans examines the writings of Roberto Bolaño and Daniel Alarcón; films by Alfonso Cuarón, Claudia Llosa, Matt Piedmont, and Joel and Ethan Coen; as well as the Netflix serials Narcos and El marginal. These widely consumed works about Latin America--equally balanced between narratives produced in the United States and in the region itself--are laden with fear, anxiety, and shame, which has an impact that exceeds the experience of reception. The negative feelings encoded in visions of Latin America become common coinage for US audiences, shaping their ideological relationship with the region and performing an affective interpellation. By analyzing the underlying melodramatic structures of these works that would portray Latin America as an implicit other, Bush examines a process of affective comprehension that foments an us/them, or north/south binary in the reception of Latin America's globalized art"--
Introduction: Speculative affects -- Staging shame just across the border: reading Bolaño in the United States -- From disgust to pity: viewing domestic labor in the films of Claudia Llosa and Alfonso Cuarón -- [indistinct chatter in Spanish]: the fear of Latin America on Netflix -- A hit and a miss: Hollywood's distressed take on the border -- Daniel Alarcón and the anxious poetics of cultural translation -- Coda: Latin America's hemispheric affects.
Includes bibliographical references and index.
Matthew Bush is associate professor of Spanish and Hispanic studies at Lehigh University.
Print version record.
JSTOR
Keywords: Bolaño, Roberto, -- 1953-2003.; Bolaño, Roberto, 1953-2003 -- Criticism and interpretation; Bolaño, Roberto, 1953-2003 -- Fictional works; Coen, Joel -- Criticism and interpretation; Coen, Ethan -- Criticism and interpretation; Coen, Ethan; Coen, Joel; Cuarón, Alfonso -- Criticism and interpretation; Llosa, Claudia, 1976-; Cuarón, Alfonso 1961-; Netflix (Firm); Latin America -- In mass media; Mass media -- Social aspects -- United States; Latin Americans -- In mass media; Other (Philosophy) in mass media; Affect (Psychology) in literature; Affect (Psychology) -- Latin America; Emotions -- Political aspects -- Latin America; Latin American literature -- History and criticism; Motion pictures -- Latin America; Melodrama; Médias -- Aspect social -- États-Unis.; Latino-Américains -- Dans les médias.; Altérité dans les médias.; Littérature latino-américaine -- Histoire et critique; Mélodrame.; ART / General; Mass media; Mass media -- Social aspects; Other (Philosophy) in mass media; Latin America; United States; Electronic books